Evaluation of umbilical cord entanglement as a predictive factor of adverse pregnancy outcomes: A meta-analysis. (December 2019) - Pergialiotis, Vasilios; Fanaki, Maria; Bellos, Ioannis; Tzortzis, Andrianos; Loutradis, Dimitrios; Daskalakis, Georgios
Abstract: The purpose of the present systematic review is to summarize current data concerning the impact of umbilical cord entanglement on adverse pregnancy outcomes. We used the Medline, Scopus, EMBASE, Cochrane Central Register of Controlled Trials CENTRAL and Google Scholar databases. We selected all observational (both prospective and retrospective) studies for inclusion. Meta-analysis of the risk ratios (RR) was performed with RevMan 5.3 software. Univariate meta-regression and leave-one-out meta-analysis was performed with Open Meta-Analyst statistical software. Trial sequential analysis was performed with the TSA software. Overall, twenty studies were included in the present study with 267, 233 pregnant women (50.103 with cord entanglement and 217, 130 controls). An increased risk of neonatal Apgar score <7 at the first minute of life was observed among cases with cord entanglement (RR = 1.75, 95% CI 1.46, 2.11). Fetal distress was significantly higher in the entanglement group (RR 1.50, 95% CI 1.33, 1.69). The incidence of fetal pH < 7.1 was also significantly higher in the entanglement group (RR 1.73, 95% CI 1.48, 2.03). Adequate power was observed in all investigated outcomes of our primary analysis after evaluating the results of the TSA analysis. Prediction intervals designated that future studies were likely to report increased risk of low Apgar score at the first minute of life, increased risk of fetal distress as well as of observing a fetal pH < 7.1. Concluding, the findings of this systematic review suggest that there is sufficient evidence to support the involvement of cord entanglement to adverse neonatal perinatal outcomes.